Advanced particle physics. Volume II: The Standard Model and Beyond - Boyarkin, O. M. (Taylor & Francis, 2011)
Helping readers understand the complicated laws of nature, Advanced Particle Physics Volume II: The Standard Model and Beyond explains the calculations, experimental procedures, and measuring methods of particle physics, particularly quantum chromodynamics (QCD). It also discusses extensions to the Standard Model and the physics of massive neutrinos.